1963
DOI: 10.1099/00221287-30-1-53
|View full text |Cite
|
Sign up to set email alerts
|

Factors which Affect the Size of the Organisms and the Optical Density of Suspensions of Pseudomonas aeruginosa and Escherichia coli

Abstract: SUMMARYWhen water-washed organisms of a strain of Pseudomonas aeruginosa were exposed to solutions of NaCl or sucrose, they shrank in size and became more dense. The optical density of suspensions increased rapidly. Pre-treatment of the organisms with various cations, surface-active agents and heat and cold, affected the reaction, and the organisms then behaved differently toward NaCl and sucrose. Some but not all of the effects observed with P. aeruginosa were also observed with a strain of Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

1964
1964
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 2 publications
4
28
0
Order By: Relevance
“…Optical density changes indicated that P. aeruginosa cells are almost impermeable to sodium chloride (Table 1). Similar results were obtained by Bernheim (1) for both sodium chloride and sucrose.…”
Section: Discussionsupporting
confidence: 79%
“…Optical density changes indicated that P. aeruginosa cells are almost impermeable to sodium chloride (Table 1). Similar results were obtained by Bernheim (1) for both sodium chloride and sucrose.…”
Section: Discussionsupporting
confidence: 79%
“…During an investigation of the effects of growth in the presence of NaCl on the production of penicillin-binding protein 2a and autolytic activity (20), it was observed that cells grown in complex medium containing 0.85 M NaCl were larger than cells grown in complex medium alone (21). Similar observations of larger cells in complex medium containing NaCl than in complex medium alone have also been reported by others (13,17).When bacterial cells such as Escherichia coli are exposed to a sudden increase in external osmotic pressure, there is initially a fast efflux of water, resulting in decreased turgor pressure, plasmolysis, and cell shrinkage (1,5,18). Mitchell and Moyle (25) have shown a similar response for S. aureus cells transferred from dilute to concentrated NaCl solutions.…”
supporting
confidence: 72%
“…When bacterial cells such as Escherichia coli are exposed to a sudden increase in external osmotic pressure, there is initially a fast efflux of water, resulting in decreased turgor pressure, plasmolysis, and cell shrinkage (1,5,18). Mitchell and Moyle (25) have shown a similar response for S. aureus cells transferred from dilute to concentrated NaCl solutions.…”
mentioning
confidence: 99%
“…Ions, however, accelerate the swelling. As shown previously (Bernheim, 1963) osmolar sucrose shrinks the organisms to the same extent as inorganic salts, but the subsequent swelling is a t a much slower rate unless a salt is added. A potassium salt increases the rate more than sodium which in turn is more effective than lithium, caesium, or rubidium.…”
Section: Discussionmentioning
confidence: 80%
“…The organisms were centrifuged down and washed twice with distilled water; in this process they lost potassium (Bernheim, 1963). They were finally suspended in distilled water and the concentration adjusted for estimation of light absorption in a Coleman junior spectrophotometer at 490 m p so that the initial optical density varied no more than 10 yo between experiments.…”
Section: Methodsmentioning
confidence: 99%